Analisis Pengelolaan Kelas untuk Menciptakan Iklim Kelas yang Kondusif di Kelas IV SDN Argopeni Tahun Ajaran 2020/2021 - Arina Ati Khusana; Suhartono Suhartono; Rokhmaniyah Rokhmaniyah (Universitas Sebelas Maret, 2021)
The objectives of the study were to explain classroom management and classroom atmosphere, to describe the constraints, and to analyze factors influencing classroom management in creating conducive atmosphere at fourth grade of SDN Argopeni. It was qualitative research method. The subjects were teachers and students. The results indicated that: (1) class management consisted of being role models in religion, being a role model for good behavior, arranging the seat of students, having audible volume and voice intonation, (e) speaking straightforward, accommodating the lesson subject to students’ abilities, creating orderliness, providing reinforcement and feedback on the responses and students learning outcomes, encouraging and appreciating students asking questions and delivering opinions, wearing modestly-dressed, explaining the syllabus, and starting and ending the learning on time. A conducive atmosphere was proven by having fun and exciting learning, having effective class organization, the teacher as a mentor, developing learning, managing the classroom, providing services and learning activities, and using media. The constraints of classroom management were the Covid-19 pandemic; (3) the factors influencing classroom management were the students and the teacher. It concludes that the teachers have applied classroom management in creating conducive atmosphere.